Magnetic cobblestone-like Cu-Fe bimetallic center MOFs as well as preparation method and application thereof

By introducing strong hydrophilic and hydrophobic functional groups on the surface of Fe-based MOFs, magnetic pebbles Cu-Fe bimetallic central MOFs were prepared, which solved the problem of poor stability of MOFs in water, and achieved efficient adsorption and separation of VOCs-type pollutants in water environments.

CN119869486AActive Publication Date: 2025-04-25ZHEJIANG UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510372139.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

The existing MOFs materials have poor stability in water and are easy to hydrolyze, which leads to further research on the adsorption of VOCs-like organic pollutants in water environments.

Method used

A magnetic pebbles Cu-Fe bimetallic central MOFs were developed, and materials with amphiphilicity and strong adsorption properties were prepared by in-situ reaction on the Fe-based MOFs surface to introduce strong hydrophilic free metal ions and strong hydrophobic aromatic amine organic ligands.

Benefits of technology

It realizes rapid adsorption and removal of VOCs-like organic pollutants in environmental water samples, has high adsorption capacity and one-step separation and purification capabilities, significantly improves the pretreatment efficiency of environmental water samples, and overcomes the problems of fragility and hydrolysis of traditional MOFs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869486A_ABST
    Figure CN119869486A_ABST
Patent Text Reader

Abstract

The invention discloses magnetic cobblestone-like Cu-Fe bimetallic center MOFs and a preparation method and application thereof.The magnetic cobblestone-like Cu-Fe bimetallic center MOFs comprise magnetic nano Fe3O4, strong-hydrophilicity free metal ions and strong-hydrophobicity aromatic amine organic ligand units, magnetic Fe-based MOFs are prepared through a microwave method, then the magnetic Fe-based MOFs serve as a matrix, and the magnetic cobblestone-like Cu-Fe bimetallic center MOFs are prepared through a microwave method. Hydrophobic aromatic amine organic ligands and strong hydrophilic free metal ions are introduced, and magnetic cobblestone-like Cu-Fe bimetallic center MOFs are generated in situ. Compared with the prior art, the magnetic cobblestone-like Cu-Fe bimetallic center MOFs have the advantages that the magnetic cobblestone-like Cu-Fe bimetallic center MOFs have amphipathicity and high adsorption capacity, the problem that MOFs in a traditional MOFs composite material are prone to fragmentation and hydrolysis is fundamentally solved, and the magnetic cobblestone-like Cu-Fe bimetallic center MOFs have more advantages in the aspects of adsorption removal and separation purification of VOCs organic pollutants in an environmental water sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional materials for pre-treatment of environmental chemical pollutants, and in particular to a magnetic pebble-like Cu-Fe bimetallic center MOFs and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) are a type of organic pollutants with a boiling point of 50~260℃ and a saturated vapor pressure of more than 133.32Pa at room temperature, mainly including benzene, toluene, xylene, chloroform, formaldehyde and trichloroethylene. This type of pollutant is toxic, some of which can cause cancer and teratogenesis, seriously threatening human life and health. For this type of organic pollutant, the research hotspot is to use adsorption method to remove VOCs in the atmosphere. The mainstream adsorption materials include activated carbon, amorphous silica, highly cross-linked polymer resins and MOFs. Compared with other traditional adsorption materials, MOFs materials have the characteristics of large specific surface area, rich and easily adjustable pore structure, diverse structural composition, strong renewability, open metal active sites, and chemical modifiability. They show excellent performance in the adsorption and removal of VOCs (Xiuquan Li, Li Zhang, Zhongqing Yang, PengWang, Yunfei Yan, Jingyu Ran. Adsorption materials for volatile organic compounds (VOCs) and the key factors for VOCs adsorption process: A review. Separation and Purification Technology, 2020, 235, 116213).

[0003] Compared with the adsorption and treatment of VOCs in the atmospheric environment, there is less research on the adsorption and removal of VOCs in water pollution caused by occasional VOCs leakage. At the same time, given the poor stability and easy hydrolysis of MOFs in water, the research on their adsorption of VOCs in water environments needs to be further developed.

[0004] During the preparation of MOFs, the reaction temperature, reaction solvent, system pH, central ions and organic ligand types of MOFs have significant effects on their adsorption performance and microstructure. In view of the hydrophilicity of free metal ions and the hydrophobicity of aromatic amine organic ligands, it is a challenge to develop an amphiphilic MOF with magnetic nano-Fe3O4, strongly hydrophilic free metal ions and strongly hydrophobic aromatic amine organic ligand units and use it for the rapid adsorption and removal of VOCs in environmental water samples. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies in the prior art and to provide a magnetic pebble-like Cu-Fe bimetallic center MOFs and a preparation method and application thereof.

[0006] The object of the present invention is achieved through the following technical scheme: a magnetic pebble Cu-Fe bimetallic center MOFs, comprising: RNH2-Fe3O4·Cu-ArNH2, wherein ArNH2 represents a strongly hydrophobic aromatic amine organic ligand, and Fe3O4 is a magnetic nano-Fe3O4.

[0007] Furthermore, the magnetic nano-Fe3O4 is one of Fe3O4 with a particle size of 10nm, 100nm, and 400nm.

[0008] Furthermore, the strongly hydrophobic aromatic amine organic ligand unit is one of 4,4'-diaminobiphenyl, 2,2'-benzidine disulfonic acid, and 4,4'-sulfonyl diphenylamine.

[0009] On the other hand, the present specification also provides a method for preparing a magnetic pebble-like Cu-Fe bimetallic center MOFs, the method comprising:

[0010] S1. Preparation of magnetic Fe-based MOFs by microwave method:

[0011] FeCl3•6H2O, ethylene glycol, anhydrous sodium acetate, and tetraethylenepentamine were added to a polytetrafluoroethylene thick-wall pressure-resistant bottle, sealed with a polytetrafluoroethylene screw plug, and ultrasonically dispersed, then transferred to a microwave reactor for reaction, cooled to room temperature, magnetically separated, washed with pure water several times until neutral, and vacuum dried to obtain magnetic Fe-based MOFs based on Fe3O4;

[0012] S2. Preparation of magnetic pebble-like Cu-Fe bimetallic center MOFs by microwave method:

[0013] Magnetic Fe-based MOFs of different particle sizes, copper acetate, aromatic amine organic ligands, strongly hydrophilic free metal ions, and 40 mL of DMF were added to a polytetrafluoroethylene thick-walled pressure-resistant bottle, sealed with a polytetrafluoroethylene screw stopper, and ultrasonically dispersed. The mixture was then transferred to a microwave reactor for reaction, cooled to room temperature, magnetically separated, washed several times with pure water until neutral, and vacuum dried to obtain magnetic pebble-like Cu-Fe bimetallic center MOFs with both amphiphilicity and strong adsorption properties.

[0014] Furthermore, the strongly hydrophilic free metal ion is Fe2 + 、Fe3 + ,Cu2 +One of them.

[0015] Furthermore, in the preparation of magnetic Fe-based MOFs using the microwave method, the mass ratio of FeCl3•6H2O and anhydrous sodium acetate is (1~3):3.

[0016] Furthermore, in the preparation of magnetic Fe-based MOFs using a microwave method, the volumes of ethylene glycol and tetraethylenepentamine are (20~60):(5~10).

[0017] Furthermore, in the preparation of magnetic pebble Cu-Fe bimetallic center MOFs by microwave method, the mass ratios of magnetic Fe-based MOFs with different particle sizes, copper acetate, aromatic amine organic ligands, and strongly hydrophilic free metal ions are (0.5~1.0): (1.0~3.0): (0.5~5.0): (0.2~2.0).

[0018] Furthermore, the temperature in the microwave reactor is 180-220° C. and 110-160° C. in the preparation of magnetic Fe-based MOFs and the preparation of magnetic pebble-like Cu-Fe bimetallic center MOFs, respectively.

[0019] On the other hand, the present specification also provides an application of a magnetic pebble-like Cu-Fe bimetallic center MOFs for the adsorption and removal of VOCs in environmental water samples.

[0020] Beneficial effects of the present invention:

[0021] (1) The preparation method of the magnetic pebble-like Cu-Fe bimetallic center MOFs of the present invention is simple, and the morphology and structure are controllable. More importantly, by in situ reaction on the surface of Fe-based MOFs, strongly hydrophilic free metal ions and strongly hydrophobic aromatic amine organic ligands are introduced into MOFs. The prepared magnetic pebble-like Cu-Fe bimetallic center MOFs not only have good amphiphilic properties, but also have high adsorption capacity for VOCs in environmental water samples. They can be used for rapid adsorption and removal of VOCs-type organic pollutants in environmental water samples and achieve one-step separation and purification, greatly improving the pretreatment efficiency of environmental water samples.

[0022] (2) Compared with traditional MOFs composite materials, the present invention fundamentally overcomes the problem of easy fragmentation and hydrolysis of MOFs in MOFs composite materials, and has more advantages in the removal and separation and purification of VOCs organic pollutants in environmental water samples. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A scanning electron microscope image of the magnetic pebble-like Cu-Fe bimetallic center MOFs provided in an embodiment of the present invention;

[0024] Figure 2The hysteresis loop of the magnetic pebble-like Cu-Fe bimetallic center MOFs provided in the embodiment of the present invention;

[0025] Figure 3 X-ray photoelectron spectrum of the magnetic pebble-like Cu-Fe bimetallic center MOFs provided in the embodiments of the present invention;

[0026] Figure 4 X-ray diffraction spectrum of the magnetic pebble-like Cu-Fe bimetallic center MOFs provided in the embodiment of the present invention;

[0027] Figure 5 The results show the adsorption performance of magnetic pebble-like Cu-Fe bimetallic center MOFs for VOCs-type organic pollutants. DETAILED DESCRIPTION

[0028] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.

[0029] The embodiment of the present invention provides a magnetic pebble Cu-Fe bimetallic center MOFs, the chemical formula of which is RNH2-Fe3O4·Cu-ArNH2, comprising magnetic nano-Fe3O4, strongly hydrophilic free metal ions, and strongly hydrophobic aromatic amine organic ligand units.

[0030] In the above scheme, the magnetic nano-Fe3O4 is at least one of Fe3O4 with a particle size of 10nm, 100nm, and 400nm.

[0031] The strongly hydrophobic aromatic amine organic ligand unit is at least one of 4,4'-diaminobiphenyl, 2,2'-benzidine disulfonic acid and 4,4'-sulfonyl diphenylamine.

[0032] The strongly hydrophilic free metal ion is Fe 2+ , Fe 3+ , Cu 2+ At least one of .

[0033] The embodiment of the present invention also provides a method for preparing a magnetic pebble-like Cu-Fe bimetallic center MOFs, comprising:

[0034] Example 1: Preparation of magnetic pebble-like Cu-Fe bimetallic center MOFs by two-step reaction

[0035] (1) 3.0 g of anhydrous sodium acetate, 20 mL of ethylene glycol, 1.0 g of FeCl3•6H2O, and 5 mL of tetraethylenepentamine were added to a polytetrafluoroethylene pressure bottle, sealed with a polytetrafluoroethylene screw plug, and ultrasonically dispersed for 20 min. The mixture was then transferred to a microwave reactor and reacted at 200 °C for 3 h. The mixture was cooled to room temperature, subjected to magnetic separation, washed with pure water several times until neutral, and dried in a vacuum oven at 60 °C for 48 h to obtain magnetic Fe-based MOFs.

[0036] (2) 0.5 g of the magnetic Fe-based MOFs prepared in step (1), 1.0 g of copper acetate, 0.5 g of aromatic amine organic ligand, 0.2 g of copper sulfate, and 40 mL of DMF were added to a polytetrafluoroethylene thick-walled pressure-resistant bottle, sealed with a polytetrafluoroethylene screw plug, and ultrasonically dispersed for 20 min. The mixture was then transferred to a microwave reactor and reacted at 130 ° C for 2 h. The mixture was cooled to room temperature, magnetically separated, washed with pure water several times until neutral, and vacuum dried at 60 ° C for 48 h to obtain magnetic pebble-like Cu-Fe bimetallic center MOFs with both amphiphilicity and strong adsorption properties.

[0037] The operating steps of Examples 1 to 18 are the same as those of Example 1, and the raw materials, raw material formulas and preparation condition parameters are shown in Table 1.

[0038] The scanning electron microscope image of the magnetic pebble-like Cu-Fe bimetallic center MOFs with both amphiphilicity and strong adsorption performance prepared in Example 1 is as follows: Figure 1 As shown in Figure 2, the magnetic Cu-Fe bimetallic center MOFs has a pebble-like structure and a relatively regular morphology. Figure 2 The hysteresis loop of the magnetic pebble Cu-Fe bimetallic center MOFs shows that the magnetic pebble Cu-Fe bimetallic center MOFs prepared in Example 1 has a strong saturation magnetization (43.98 emu / g), which enables it to achieve efficient directional movement under the action of an external magnetic field and is conducive to the recycling of materials. Figure 3 As shown, the bonding energies of carbon spectrum (C 1s), oxygen spectrum (O 1s), nitrogen spectrum (N 1s) and iron spectrum (Fe2p) in the magnetic pebble-like Cu-Fe bimetallic center MOFs obtained in Example 1 are 286.6 eV, 530.2 eV, 399.8 eV and 710.9 eV, respectively, indicating that the hydrophobic aromatic amine group is successfully immobilized in the magnetic Cu-Fe bimetallic center MOFs. In addition, Figure 4As shown, the XRD spectrum of the magnetic pebble-like Cu-Fe bimetallic center MOFs in Example 1 shows that the 2θ angles are at 30.1°, 35.5°, 42.9°, 57.1° and 62.7°, corresponding to the (220), (311), (400), (422), (511) and (440) crystal planes of Fe3O4, respectively; the 2θ angles are at 43.8°, 50.8° and 73.9°, corresponding to the (111), (200) and (220) crystal planes of Cu, respectively, further indicating that the magnetic pebble-like Cu-Fe bimetallic center MOFs were successfully prepared.

[0039] Table 1 Raw material components and preparation parameters of Examples 1 to 18 of the present invention

[0040]

[0041] Example 19: Evaluation of the adsorption performance of magnetic pebble-like Cu-Fe bimetallic center MOFs

[0042] The adsorption performance of the magnetic pebble-like Cu-Fe bimetallic center MOFs prepared in Example 1 of the present invention was investigated. 10.0 mg of VOCs standard substances such as benzene, toluene, xylene, chloroform, formaldehyde and trichloroethylene were accurately weighed into 6 10 mL volumetric flasks, dissolved with a small amount of methanol, and then diluted to the mark with methanol to prepare a 1.0 g / L standard stock solution, which was stored in a refrigerator at 4°C for later use. 50 mL of a mixed standard solution with a concentration of 100 mg / L was prepared using the above-mentioned VOCs standard stock solutions, and 20 mg of the magnetic pebble-like Cu-Fe bimetallic center MOFs prepared in Example 1 was added. The adsorption temperature was 30°C, and magnetic stirring or constant temperature oscillation was performed for 24 hours. After the adsorption was completed, magnetic separation was performed, and the concentrations of VOCs such as residual benzene, toluene, xylene, chloroform, formaldehyde and trichloroethylene in the supernatant were determined by GC-MS / MS, and the adsorption capacity was calculated according to formula (1). The results are as follows: Figure 5 shown.

[0043] (1)

[0044] q is the adsorption capacity (mg / g), C0 is the initial concentration of VOCs in the water sample (mg / L), C e is the concentration of VOCs in the water sample at adsorption equilibrium (mg / L), V is the volume of the water sample (mL), and m is the mass of the magnetic pebble-like Cu-Fe bimetallic center MOFs (g).

[0045] Depend on Figure 5It can be seen that the magnetic pebble-like Cu-Fe bimetallic center MOFs have a high adsorption capacity for VOCs-type organic pollutants, and have great application potential in the adsorption and removal of VOCs-type organic matter in water environment pollution caused by occasional VOCs leakage.

[0046] On the other hand, an embodiment of the present invention also provides an application of the above-mentioned magnetic pebble Cu-Fe bimetallic center MOFs in the adsorption and removal of VOCs organic pollutants in environmental water samples, including: transferring 50-100mL of water sample into a 250mL flat-bottom flask, adding 20-50mg of magnetic pebble Cu-Fe bimetallic center MOFs, and adsorbing under constant temperature oscillation for 12-24h at 25℃-40℃. After the adsorption is completed, magnetic separation is performed to obtain a supernatant; the supernatant is analyzed by gas chromatography-tandem mass spectrometry to obtain the content of residual VOCs in the water sample, and then the adsorption rate of VOCs in the water sample by the magnetic pebble Cu-Fe bimetallic center MOFs is calculated.

[0047] Those skilled in the art will readily appreciate other embodiments of the present application after considering the description and practicing the contents disclosed herein. The present application is intended to cover any modification, use or adaptation of the present application, which follows the general principles of the present application and includes common knowledge or customary techniques in the art that are not disclosed in the present application. The description and examples are intended to be exemplary only, and the true scope and spirit of the present application are indicated by the claims.

[0048] It should be understood that the above general description and the detailed description below are only exemplary and explanatory and cannot limit the present application. The present application is not limited to the precise structure described above and shown in the drawings, and various modifications and changes can be made without departing from the scope thereof. The scope of the present application is limited only by the attached claims.

Claims

1. A magnetic pebble-like Cu-Fe bimetallic center MOFs, characterized in that: include: RNH2-Fe3O4·Cu-ArNH2, wherein ArNH2 represents a strongly hydrophobic aromatic amine organic ligand, and Fe3O4 is magnetic nano-Fe3O4.

2. A magnetic pebble-like Cu-Fe bimetallic center MOFs according to claim 1, characterized in that: The magnetic nano-Fe3O4 is one of Fe3O4 with a particle size of 10nm, 100nm, and 400nm.

3. A magnetic pebble-like Cu-Fe bimetallic center MOFs according to claim 1, characterized in that: The strongly hydrophobic aromatic amine organic ligand unit is one of 4,4'-diaminobiphenyl, 2,2'-benzidine disulfonic acid and 4,4'-sulfonyl diphenylamine.

4. A method for preparing the magnetic pebble-like Cu-Fe bimetallic center MOFs according to any one of claims 1 to 3, characterized in that: The method includes: S1. Preparation of magnetic Fe-based MOFs by microwave method: FeCl3•6H2O, ethylene glycol, anhydrous sodium acetate, and tetraethylenepentamine were added to a polytetrafluoroethylene thick-wall pressure-resistant bottle, sealed with a polytetrafluoroethylene screw plug, and ultrasonically dispersed, then transferred to a microwave reactor for reaction, cooled to room temperature, magnetically separated, washed with pure water several times until neutral, and vacuum dried to obtain magnetic Fe-based MOFs based on Fe3O4; S2. Preparation of magnetic pebble-like Cu-Fe bimetallic center MOFs by microwave method: Magnetic Fe-based MOFs of different particle sizes, copper acetate, aromatic amine organic ligands, strongly hydrophilic free metal ions, and 40 mL of DMF were added to a polytetrafluoroethylene thick-walled pressure-resistant bottle, sealed with a polytetrafluoroethylene screw plug, and ultrasonically dispersed. The mixture was then transferred to a microwave reactor for reaction, cooled to room temperature, magnetically separated, washed with pure water several times until neutral, and vacuum dried to obtain magnetic pebble-like Cu-Fe bimetallic center MOFs with both amphiphilicity and strong adsorption properties.

5. The method for preparing a magnetic pebble Cu-Fe bimetallic center MOFs according to claim 4, characterized in that: The strongly hydrophilic free metal ion is Fe2 + 、Fe3 + ,Cu2 + One of them.

6. The method for preparing the magnetic pebble Cu-Fe bimetallic center MOFs according to claim 4, characterized in that: In the microwave method for preparing magnetic Fe-based MOFs, the mass ratio of FeCl3•6H2O to anhydrous sodium acetate is (1~3):

3.

7. The method for preparing the magnetic pebble Cu-Fe bimetallic center MOFs according to claim 4, characterized in that: In the microwave method for preparing magnetic Fe-based MOFs, the volume ratio of ethylene glycol to tetraethylenepentamine is (20-60): (5-10).

8. The method for preparing the magnetic pebble Cu-Fe bimetallic center MOFs according to claim 4, characterized in that: In the microwave method for preparing magnetic pebble-like Cu-Fe bimetallic center MOFs, the mass ratios of magnetic Fe-based MOFs with different particle sizes, copper acetate, aromatic amine organic ligands, and strongly hydrophilic free metal ions are (0.5~1.0): (1.0~3.0): (0.5~5.0): (0.2~2.0).

9. The method for preparing the magnetic pebble Cu-Fe bimetallic center MOFs according to claim 4, characterized in that: The temperature in the microwave reactor is 180-220° C. and 110-160° C. in the preparation of magnetic Fe-based MOFs and the preparation of magnetic pebble-like Cu-Fe bimetallic center MOFs, respectively.

10. An application of the magnetic pebble-like Cu-Fe bimetallic center MOFs according to any one of claims 1 to 3, characterized in that: Used for adsorption and removal of VOCs in environmental water samples.

Citation Information

Patent Citations

  • Superparamagnetic nanoparticle Fe3O4@SiO2@PSA modified by PSA and preparing method and application thereof

    CN104525128A

  • Solid magnetic heavy metal ion separation material and preparation method thereof

    CN108057427A

  • Preparation method of magnetic covalent organic framework molecularly imprinted polymer for separating anthocyanin

    CN111269454A

  • Application of magnetic carboxylated covalent organic framework material as magnetic solid-phase extraction adsorbent

    CN114130374A

  • Magnetic covalent nano material as well as preparation method and application thereof

    CN114632497A